Effects of variations in signaling of authority and type of sanction, on obedience - Luna, Edwin (2017)
Objective: to analyze the differential effect of variations in the signaling of authority and type of sanction administered by it, on the obedience in university students. Method: an intrasubject design was used and nine university students were involved. An experiment that allows to observe the effect of four experimental conditions in rule transgressions was designed. Conditions were created starting from variables of signaling of authority and type of sanction: not designated authority and negative sanction; designated authority and negative sanction; not designated authority and positive sanction; and designated authority and positive sanction. Results: It was found a bigger amount of transgressions (disobedience) in designated authority conditions, and less amount of transgressions (obedience) in not designated authority conditions. Conclusion: When positive or negative sanctions are applied in conditions of not signaling of authority, increases the probability of obedient behavior.